School programs of coexistence, conflict mediation and peace (Journal of Parents and Teachers, 2012)
This article talks about how bad results give the current schoolar programs. The author says that its necessary to solve and mediate in the problems so that children learn how important is to have good and peacful relationships with people.
Keywords: Mediation; schoolar programs; problems; personal relationships.